2018
DOI: 10.1161/circheartfailure.118.005191
|View full text |Cite
|
Sign up to set email alerts
|

Incident Atrial Fibrillation Is Associated With MYH7 Sarcomeric Gene Variation in Hypertrophic Cardiomyopathy

Abstract: Background Although atrial fibrillation (AF) is common in hypertrophic cardiomyopathy (HCM) patients, the relationship between genetic variation and AF has been poorly defined. Characterizing genetic subtypes of HCM and their associations with AF may help to improve personalized medical care. We aimed to investigate the link between sarcomeric gene variation and incident AF in HCM patients. Methods and Results Patients from the multinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 40 publications
4
30
0
2
Order By: Relevance
“…Atrial brillation tended to be more prevalent in the MYH7 group in our study. This nding is consistent with previous studies [16,30], which reported a higher incidence of atrial brillation in patients with MYH7 mutation in comparison to other HCM patients. Since the development of atrial brillation was associated with risk factors such as LA enlargement, LV wall thickness, and LV out ow tract obstruction, these results suggest that patients with MYH7 mutation present with a more severe clinical phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…Atrial brillation tended to be more prevalent in the MYH7 group in our study. This nding is consistent with previous studies [16,30], which reported a higher incidence of atrial brillation in patients with MYH7 mutation in comparison to other HCM patients. Since the development of atrial brillation was associated with risk factors such as LA enlargement, LV wall thickness, and LV out ow tract obstruction, these results suggest that patients with MYH7 mutation present with a more severe clinical phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with identified sarcomere gene variants are, therefore, at an increased risk of developing AF earlier in life. Furthermore, it has been demonstrated that variation in the MYH7 gene is associated with incident AF, independent of established risk factors of AF in the general population, age and LA size 16 . Our results likewise show AF is independently associated with age, LA area, and MYH7 variants compared with MYBPC3 .…”
Section: Discussionsupporting
confidence: 76%
“…There is marked clinical heterogeneity in HCM, and although variable penetrance and expressivity are hallmarks of the disease, recognition of sarcomere‐positive and nonfamilial forms of disease as distinct subgroups may further explain the observed spectrum of disease 14,15 . There is also emerging data to suggest that a patient's underlying genetics may play an important role in AF development 14,16 . We report the frequency of AF in patients with inherited cardiomyopathies and inherited arrhythmia syndromes, including factors associated with AF in those with sarcomere‐positive HCM.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, these HCM-enriched surface regions are particularly noteworthy of study. Interestingly, recent work [50] showed that incident atrial fibrillation is associated with HCM mutations in β-cardiac myosin, and that the incidence of new-onset atrial fibrillation was considerably higher in those patients with mutations in the HCM-enriched surface regions compared to those with mutations in other regions of myosin.…”
Section: The Second Perspective: Hypercontractility Results From An Imentioning
confidence: 99%